Gadolinium deposition in the brain is related to various contrast agents: a matched case–control study. Issue 4 (April 2022) - Bi, Q.; Li, H.; Du, J.; Li, H.; Li, Q.; Wang, J.; Huang, Y.; Gong, X.
Abstract : AIM: To assess the relationship between gadolinium deposition in the brain and various gadolinium-based contrast agents (GBCAs) and to explore confounding variables. METHODS: The study group included 87 patients with multiple enhanced brain magnetic resonance imaging (MRI) examinations of which 48 patients were in the linear GBCA group (33 patients in gadopentetate dimeglumine group and 15 patients in gadobenate dimeglumine group) and 39 patients in the macrocyclic GBCA group (22 patients in gadobutrol group and 17 patients in gadoterate meglumine group). The control group included 87 normal participants who were matched regarding age, sex, MRI machine and imaging sequences to the study cohort. T1 signal intensity (SI) ratios of the dentate nucleus to the pons (DN/pons) and of the globus pallidus to the frontal white matter (GP/FWM) in both groups were calculated and compared. The relationships between SI ratios and confounding variables were analysed. RESULTS: Significant differences were detected between two linear GBCA groups and control groups in T1 SI ratios of the DN/pons and GP/FWM (all p< 0.001). There were no differences for two the macrocyclic GBCA groups compared with matching control groups (all p> 0.05). T1 SI ratios of the linear GBCA group were significantly higher than those of the macrocyclic GBCA group ( p< 0.001). In the linear GBCA group, the T1 SI ratios of the DN/pons correlated moderately positively with the number of GBCA administrations ( r =0.643, p< 0.001), and MRI machine and sequence used. CONCLUSIONS: Increased T1 SI could be observed after repeated administrations of linear GBCA. T1 SI of the DN correlated with the number of linear GBCA administrations, and detection might be affected by MRI machine and sequence.